Roland Barthes' Semiotic Analysis of the Lyrics of the Song Ḥājah Mistakhbiyah by Muḥammad Ḥamāki (Denotation, Connotation and Myth) - Rustam, Rustam; Ahmad, Muhsin; Pallawagau, Baso (CV. Rayyan Dwi Bharata, 2025)
This article analyzes the lyrics of the song